Optimization of bovine oocyte cryopreservation: membrane fusion competence and cell death of linoleic acid-in vitro matured oocytes subjected to vitrification - Ríos, Glenda L.; Suqueli García, María Florencia; Manrique, Rodrigo J.; Buschiazzo, Jorgelina (Frontiers in Veterinary Science, 2025)
Long-term conservation of livestock female genetic resources has led to increased interest in oocyte cryopreservation. However, the challenges of preserving large-volume cells and the lack of standardization in vitrification media and cryo-devices for domestic species remain critical areas of ongoing research. This study aimed to assess the impact of in vitro maturation medium composition and vitrification devices on cell death and membrane fusion competence of vitrified bovine oocytes, comparing a chemically undefined versus a synthetic maturation medium supplemented with linoleic acid (LA), and using both tubular (open-pulled straw) and surface vitrification devices (Cryotech®). In vitro maturation of bovine oocytes under serum-free conditions improved post-vitrification survival, particularly by preserving membrane integrity. Additionally, oocytes matured in a synthetic medium containing epidermal growth factor and hyaluronic acid, and vitrified using a surface device, exhibited increased viability and reduced caspase activation. Supplementation of this medium with 43 μM LA did not compromise oocyte viability or apoptotic status. In contrast, higher concentrations (100 μM) induced significant apoptosis and disrupted membrane integrity, impairing tolerance to cryoprotectant agents. We also identified two distinct localization patterns of the transcription factor OCT4 in matured oocytes, with vitrification promoting the diffuse pattern. Supplementation with LA was insufficient to mitigate the effects of vitrification on OCT4 distribution. Unlike 43 μM, maturation with 100 μM LA increased the proportion of oocytes exhibiting the diffuse OCT4 pattern following exposure to cryoprotectant agents under non-vitrified conditions. Zona pellucida-free oocytes co-incubated with sperm demonstrated that 43 μM LA better preserved the original sperm adhesion and fusion pattern post-vitrification, although fertilization rate was not improved. These findings demonstrate that optimized maturation conditions—comprising serum-free media, membrane fluidity-modulating lipids (43 μM LA), and the use of surface cryo-devices—significantly enhance oocyte quality, post-warming survival, and fusion competence, all of which are critical for improving fertilization outcomes following vitrification.